2019
DOI: 10.9734/ajaees/2019/v31i430136
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Farmers’ Choice among Alternative Rice Output Markets in Kano State, Nigeria

Abstract: The aim was to analyze the output market outlets accessible to rice farmers and determinants of farmers’ choice among alternative rice production in Kano State, Nigeria. Primary data were collected from 164 rice farmers with the aid of structured questionnaire. This study was conducted in Kura, Garun Malam and Bunkure Local Government Areas of Kano State during 2015 cropping season. A multistage sampling techniques were used for data collection through the use of structured questionnaire. The ordered probit  m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
1
2
Order By: Relevance
“…This could negatively affect the acceptance of IURPPs in the area. The findings of this study is dissimilar with Abdulrahman et al (2018) who observed in their study that 76% of the rice farmers have farm size ranging from 0.1-5 ha with an average of 4 ha. However the result concurs with Onyeneke (2017) who found that average farm size of the farmers in Imo State, Nigeria was 1.8 ha.…”
Section: Results and Discussion Socio-economic Characteristics Of The...contrasting
confidence: 99%
See 1 more Smart Citation
“…This could negatively affect the acceptance of IURPPs in the area. The findings of this study is dissimilar with Abdulrahman et al (2018) who observed in their study that 76% of the rice farmers have farm size ranging from 0.1-5 ha with an average of 4 ha. However the result concurs with Onyeneke (2017) who found that average farm size of the farmers in Imo State, Nigeria was 1.8 ha.…”
Section: Results and Discussion Socio-economic Characteristics Of The...contrasting
confidence: 99%
“…This could help them understand the value of IURPPs even if it is complex which may encourage acceptance. The finding differs with Abdulrahman et al (2018) discovered that the mean years of schooling of the respondents were 5 years and largely skewed towards the non-formal education. The finding showed that farmers have average household size of 7 persons which is equivalent to national average.…”
Section: Results and Discussion Socio-economic Characteristics Of The...contrasting
confidence: 77%
“…This finding indicates that farmers in the study area had more responsibilities; this makes them work hard to cater to family needs, hence could produce more NERICA 1 rice because of high yield with low inputs requirement. This finding is in agreement with Abdulrahman et al (2018) who opined that married respondents with an additional member of households could encourage income diversification. The result showed that the larger part (53.7%) of respondents had no access to any amount of credit.…”
Section: Socio-economic Characteristics Of Respondentssupporting
confidence: 92%
“…This means that the respondents were typical smallholders which could negatively affect mechanization and commercialization. However, Abdulrahman et al (2018) and Onyeneke (2017) also differ with this result saying rice farmers operated average farm size of 4 ha and 1.8 ha in Kano and Imo States of Nigeria, respectively.…”
Section: Farmers' Age Household Size Farm Size Farming Experience And...mentioning
confidence: 80%